1987
DOI: 10.1177/0013164487471024
|View full text |Cite
|
Sign up to set email alerts
|

EXACON: A Fortran 77 Program for the Exact Analysis of Single Cells in a Contingency Table

Abstract: A program named EXACON is presented which performs exact cellwise analyses of two-way contingency tables. EXACON is written in FORTRAN 77 and is interactive. One-tailed probabilities are computed for the observed frequency of each cell according to two different probability models, one being Fisher's exact test for a 2 x 2 table. Despite the fact that exact probabilities are computed, EXACON does not demand much computer time even for fairly large samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 7 publications
0
61
0
Order By: Relevance
“…To test the hypotheses, the observed frequency in each cell was compared with the frequency that should be expected by chance alone, and one-tailed probabilities were computed according to the fixed-margins model using EXACON (Bergman & El-Khouri, 1987).…”
Section: Cluster Analysismentioning
confidence: 99%
“…To test the hypotheses, the observed frequency in each cell was compared with the frequency that should be expected by chance alone, and one-tailed probabilities were computed according to the fixed-margins model using EXACON (Bergman & El-Khouri, 1987).…”
Section: Cluster Analysismentioning
confidence: 99%
“…The gender distribution in the ten clusters is shown in Table 3. To test the hypothesis that girls would be overrepresented in the depression-related clusters, the observed frequency was compared with the frequency that should be expected by chance alone, and one-tailed probabilities were computed according to the fixed-margins model using EXACON [33]. The results showed that the girls were overrepresented in both the Depression cluster (observed frequency 20, expected frequency 13.5, χ 2 = 3.13, P = .009) and in the Mild/moderate depression cluster (observed frequency 53, expected frequency 40.5, χ 2 = 3.86, P = .003).…”
Section: Gender Comparison Between the Clustersmentioning
confidence: 99%
“…The clusters significantly related to social network centrality [ 2 (10, 184) = 20.58, p < .05]. The overall relationship was probed with Fisher's exact probability (FEP) tests, which provide cell-specific probabilities (Bergman and El-Khouri, 1987). These tests showed that three cells drove the effect.…”
Section: Resultsmentioning
confidence: 99%